Pattern of Inappropriate use of Topical Corticosteroid and Cutaneous Adverse Effects at a Tertiary Level Hospital in Kathmandu - Bhandari, Sabina; Paudel, Upama (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Introduction: Topical corticosteroids are anti-inflammatory, immunosuppressive, and anti-proliferative drugs with profound efficacy. As it provides rapid relief, it is used for a wide spectrum of dermatological conditions. Rampant use of topical corticosteroids due to their easy availability gives rise to difficult-to-treat cutaneous adverse effects. Objectives: To determine the pattern of inappropriate use of topical corticosteroids and cutaneous adverse effects Materials and Methods: This was a hospital based cross-sectional prospective study conducted among 84 participants in the Department of Dermatology, Tribhuvan University Teaching Hospital, Kathmandu, from October 2020 to September 2021. Ethical clearance was obtained from the Institutional Review Committee. The participants fulfilling the inclusion criteria were included in the study. Results: Out of 84 cases, 59.5% were females and 40.5% were males. The mean age of participants was 30.4±9.1years. Dermatophytoses (71.4%) were the most common cause of inappropriate use of topical corticosteroids. The most common adverse effect was tinea incognito (23.8%). The most potent class (60%) of topical corticosteroids were misused. Most of the participants used topical steroids either for the duration of 1 week to 1 month ( 23.8%) or for more than 12 months (23.8%). Conclusion: Inappropriate topical corticosteroid use is a common problem due to its easy accessibility, resulting in several difficult-to-treat cutaneous adverse effects. So, awareness-raising activities regarding the proper use of corticosteroids have to be conducted.